2020
DOI: 10.1017/s147895151900110x
|View full text |Cite
|
Sign up to set email alerts
|

Process of therapeutic changes in Meaning-Centered Group Psychotherapy adapted to the Portuguese language: A narrative analysis

Abstract: AbstractObjectiveThe aim was to understand the processes of therapeutic changes in Meaning-Centered Group Psychotherapy (MCGP) in a Portuguese sample.MethodAdult cancer patients with distress motivated to participate in MCGP were identified; descriptive and narrative analyses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…This process fosters a deeper level of introspection among patients, resulting in a fresh perspective, a clarified life purpose, and a sense of meaning by prioritizing what truly matters to them. These findings are further corroborated by the results of qualitative studies involving the application of MCGP to Portuguese cancer patients and Spanish patients dealing with advanced cancer ( 22 , 31 ). Most patients not only appreciated the overall value of the MCGP but also found significant benefit in the individual themes ( 32 , 33 ).…”
Section: Discussionsupporting
confidence: 62%
“…This process fosters a deeper level of introspection among patients, resulting in a fresh perspective, a clarified life purpose, and a sense of meaning by prioritizing what truly matters to them. These findings are further corroborated by the results of qualitative studies involving the application of MCGP to Portuguese cancer patients and Spanish patients dealing with advanced cancer ( 22 , 31 ). Most patients not only appreciated the overall value of the MCGP but also found significant benefit in the individual themes ( 32 , 33 ).…”
Section: Discussionsupporting
confidence: 62%
“…The results of a study showed that the meaning of life for cancer patients in Iran induces their personal growth [14]. Another study found that the meaning of life for cancer patients in Portugal improved their relationships with others and their functioning [15]. A study in the United States showed that the meaning of life for cancer patients improved their connection with friends and family members and strengthened their faith in God [16].…”
Section: Introductionmentioning
confidence: 99%
“…Since cultural differences may exist regarding the meaning of cancer as an event that interrupts one's own existential journey, the adaptation of group meaning-centered interventions and MCP have been proposed, taking into account the culturally bound representation of existence and meaning (e.g., Leng et al, 2018 in China; da Ponte et al, 2020 in Portugal). In Italy, only a few data are available in the area of the meaning of the disease and the way cancer patients interpret their experience of illness.…”
Section: Introductionmentioning
confidence: 99%